2018
DOI: 10.1111/bph.14457
|View full text |Cite
|
Sign up to set email alerts
|

Icariin protects cardiomyocytes against ischaemia/reperfusion injury by attenuating sirtuin 1‐dependent mitochondrial oxidative damage

Abstract: Pretreatment with icariin protected cardiomyocytes from I/R-induced oxidative stress through activation of sirtuin-1 /FOXO1 signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 84 publications
0
55
0
Order By: Relevance
“…Cardiac Myocyte Apoptosis. Previous studies confirmed that oxidative stress and subsequent cardiac myocyte apoptosis play central roles in the initiation and progression of myocardial I/R injury [9,35]. We then assessed the role of Hotair in I/R-induced oxidative stress and cardiac myocyte apoptosis.…”
Section: Hotair Protects Against I/r-induced Oxidative Stress Andmentioning
confidence: 89%
See 1 more Smart Citation
“…Cardiac Myocyte Apoptosis. Previous studies confirmed that oxidative stress and subsequent cardiac myocyte apoptosis play central roles in the initiation and progression of myocardial I/R injury [9,35]. We then assessed the role of Hotair in I/R-induced oxidative stress and cardiac myocyte apoptosis.…”
Section: Hotair Protects Against I/r-induced Oxidative Stress Andmentioning
confidence: 89%
“…H9c2 cells were purchased from ATCC (Manassas, VA, USA) and cultured in Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (FBS). To imitate the I/R injury in vitro, H9c2 cells were preincubated in Krebs buffer with pyruvate (5 μM) and sodium sulfite (50 μM) in the humidified incubator (5% CO 2 /95% N 2 , 37°C) for 2 hours, which were then replaced with fresh DMEM containing 10% FBS under normoxic conditions (5% CO 2 /95% air, 37°C) for additional 24 hours to generate hypoxia/reoxygenation (H/R) cell model according to previous studies with a little modifications [34,35]. To notify the role of BRD4 in vitro, H9c2 cells were incubated with small interfering RNA against BRD4 (siBrd4, 50 nM; #RSS338226, Thermo Fisher Scientific) using Lipofectamine RNAiMAX (Invitrogen) for 24 hours before H/R stimulation [32].…”
Section: Measurement Of Cardiac Troponin I (Ctni) N-terminal B-type mentioning
confidence: 99%
“…Results of the MTT assay and LDH release demonstrated that mPEG-ICA could decrease cell damage induced by OGD and that mPEG-ICA NPs could release ICA completely from particles. Previous studies have demonstrated that cardiomyocyte ischaemia leads to cytochrome C release from dysfunctional mitochondrial into the cytosol, then cytochrome C initiates apoptosis, which results in functional cell loss and decreased heart function [45,46].Therefore, anti-apoptosis is a new strategy for treating ischaemic cardiomyopathy. Traditional Chinese medicine, such as berberine, tetrandrine and resveratrol, can improve heart function and reverse cardiac remodelling by reducing apoptosis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Icariin (C 33 H 40 O 15 , ICA) is a flavonoid monomer isolated from the herb Epimedium, and it has garnered attention for its prospects in pharmacology, including its cardioprotective functions (Zhou et al, 2014;Meng et al, 2015). Icariin protects cardiomyocytes against oxidative stress by activating sirtuin-1 (Wu et al, 2018), thereby alleviating oxidative stress-induced cardiac apoptosis via mitochondrial protection (Song et al, 2016), and protects cardiomyocytes from apoptosis induced by hypertrophy via inhibition of ROS-dependent JNK (Zhou et al, 2014). However, the protective effect of icariin against DCM has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%